2020
DOI: 10.3390/antiox9030229
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Selected Bioactive Compounds in the Prevention of Alzheimer’s Disease

Abstract: Neurodegeneration is a feature of many debilitating, incurable age-dependent diseases that affect the nervous system and represent a major threat to the health of elderly persons. Because of the ongoing process of aging experienced by modern societies, the increasing prevalence of neurodegenerative diseases is becoming a global public health concern. A major cause of age-related dementia is Alzheimer’s disease (AD). Currently, there are no effective therapies to slow, stop, or reverse the progression of this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 78 publications
0
54
0
1
Order By: Relevance
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…It consists in the accumulation of amyloid beta (Aβ) due to genetic defects (i.e., APP, presenilin 1, presenilin 2), environmental factors, and other stressors. These senile plaques induce an immune response, leading to inflammation, tau hyperphosphorylation, and its aggregation in tangles [12] that lead to neuron degeneration and death, and impairing neurotransmission in many brain regions [13].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Observational studies, indirectly confirming the neuroprotective effects of olive oil, showed that MD is linked to a reduced risk of AD [178,188], independently from other factors such as sex, education or APOE gene allele. This diet has been promoted by researchers, clinicians and institutions as a model for healthy eating mainly because it provides a significant source of antioxidants [189].…”
Section: Extra Virgin Olive Oil (Evoo)mentioning
confidence: 88%
“…Again by virtue of its antioxidant properties, it has neuroprotective potential; indeed it protects from neurodegenerative diseases such as AD and, more generally, dementias and Parkinson's disease, especially in combination with other active ingredients, such as lutein, astaxanthin and zeaxanthin [177]. Many studies show that free radical level and amyloid-induced mitochondrial dysfunction lowered [178] after LYC treatment. Recently, a study demonstrated that 8 weeks of LYC treatment reversed MDA increase and glutathione peroxidase decrease in serum of tau transgenic mice expressing P301L mutation [179][180][181].…”
Section: Lycopenementioning
confidence: 99%